(untitled) (Journal of Reviews on Global Economics, 2018)
The complexity of trade finance instruments associated with need for many accompanying documents, constant coordination are problems of this process. Successful development of trade finance instruments depend on improvement of software and implement blockchain solutions that enable companies to unite and through partnerships and process automation to accelerate cash flow and documentation throughout supply chain. The paper aims to examine areas and ways of blockchain application in trade finance and to identify key aspects of improving transactions process. We present possible interaction of participants with digital letters of credit and factoring with blockchain application and display its effect on key trade finance instruments. Moreover, we identifies a number of problems, implementation solutions of which will lead to further more efficient application of technology in supply chain finance. The achieving these goals will lead to further more effective application of blockchain in financing of supply chain. Blockchain with a high level of functionality and security in trade finance processes reduces processing time for documents, transaction costs, expanding number of participants and increases level of transparency.